Genetic and phenotypic evaluation of Candida albicans strains isolated from subgingival biofilm of diabetic patients with chronic periodontitis - Sardi, Janaina C O; Duque, Cristiane; Höfling, José F; Gonçalves, Reginaldo B (Medical mycology (Oxford), 2012)
Candida spp. are commensal microorganisms that are part of the microflora of different sites within the oral cavity. In healthy subjects, who have an unaltered immunological status, these yeasts do not cause disease. However, in immunosuppressed individuals whose condition may have been caused by diabetes mellitus, Candida spp. can express different virulence factors and may consequently become pathogenic. Studies have detected the presence of Candida spp. in periodontal sites of patients with chronic periodontitis, especially those that are immunologically compromised. However, the role of these microorganisms in the pathogenesis of periodontal disease is still unknown. The objectives of this study were: (1) to isolate and identify Candida albicans strains from subgingival sites of diabetic patients with chronic periodontitis; (2) to evaluate the following virulence factors; colony morphology, proteinase, phospholipase and hemolysin activities and cell surface hydrophobicity (CSH) under different atmospheric conditions; and (3) to determine the genetic patterns of these C. albicans isolates. Microbial samples were collected from subgingival sites and seeded on CHROMagar for subsequent identification of C. albicans by polymerase chain reaction (PCR). For the phenotypic tests, all strains of C. albicans were grown under reduced oxygen (RO) and anaerobiosis (ANA) conditions. Genotypes were defined by the identification through PCR of the transposable introns in the 25S rDNA. The results obtained relative to virulence factors were analyzed according to the atmospheric condition or genetic group, using Chi-square and Wilcoxon non-parametric tests. In this study, 128 strains were identified as C. albicans and of these, 51.6% were genotype B, 48.4% were genotype A and Genotype C was not found. Most of the strains were alpha-hemolytic in both atmospheric conditions, without a statistical difference. However, when comparing the genotypes, 46.1% of the genotype A strains were beta-hemolytic. In relation to colony morphology, 100% of the strains under ANA showed rough colonies, which were especially prevalent in genotype A isolates. In contrast, most of the colonies were smooth under RO. C. albicans strains did not produce proteinase and phospholipase activity in the total absence of oxygen. In RO, most strains had high proteinase activity and were positive by phospholipase tests (P < 0.05). Hydrophobicity was higher in anaerobiosis and was noted mainly for genotype A isolates. In conclusion, environmental oxygen concentration influenced the virulence factors of C. albicans strains isolated from subgingival sites of diabetic and periodontal patients. In addition, genotype A seems to be more virulent based on the phenotypic tests evaluated in this study.